Inquiry based mathematics education and the development of learning trajectories - Artigue, Michèle; Bosch, Marianna; Doorman, Michiel; Juhász, Péter; Kvasz, Ladislav; Maass, Katja (Teaching Mathematics and Computer Science, 2020)
This article is based on the panel on inquiry based mathematics education and the development of learning trajectories held at the VARGA 100 Conference. After an introduction presenting the theme and organization of the panel, this article focuses on the diversity of conceptualizations of inquiry based education existing today in mathematics education and their influence on the vision and development of learning trajectories. More precisely, it considers the conceptualizations respectively associated with Realistic Mathematics Education, Genetic Constructivism, Tamás Varga’s educational approach and the Anthropological Theory of the Didactic, presented by the panellists, and also shows the efforts undertaken in European projects to reach consensusal visions. Subject Classification: 97C30Q, 97D10, 97D20, 97D30, 97D40, 97D50